Repeated Contrast Administration Is Associated With Low Risk of Postcontrast Acute Kidney Injury and Long‐Term Complications in Patients With Severe Chronic Kidney Disease. Issue 3 (14th December 2015) - Winther, S.; Svensson, M.; Jørgensen, H. S.; Birn, H.; Bøtker, H. E.; Ivarsen, P.; Bøttcher, M.
Abstract : Patients with chronic kidney disease (CKD) frequently require radiographic examinations. We investigated the impact of repeated contrast administrations on short‐ and long‐term kidney function and mortality in kidney transplantation candidates. In a prospective study, 81 predialysis transplantation candidates underwent computed tomography angiography (CTA) and invasive coronary angiography (ICA) as part of a pretransplant cardiovascular evaluation. Postcontrast plasma creatinine (P‐creatinine) changes were compared with a precontrast control period. We identified postcontrast acute kidney injury (AKI) in 10 patients (13%) after CTA and in two patients (3%) after ICA. Compared with the control period, relative changes in P‐creatinine were significantly higher after CTA (p < 0.001) and ICA (p < 0.01). Diabetic kidney failure (p < 0.05) and contrast dose >0.8 mL/kg (p < 0.001) were associated with increases in P‐creatinine. All cases of postcontrast AKI were reversible, and we found no differences between the progression rates of the kidney failure during 12 months before and after contrast exposure (p = 0.56). In a Cox regression analysis, creatinine changes after CTA or ICA were not associated with increased need for dialysis treatment or mortality. Contrast exposure and transient postcontrast AKI did not increase the risk of accelerated CKD progression or the time to initiation of dialysis or death. Abstract : Contrast exposure and transient postcontrast acute kidney injury does not impact the prognosis of kidney transplantation candidates referred for cardiovascular evaluation.